Multiscale Graphene‐Based Materials for Applications in Sodium Ion Batteries. Issue 8 (21st January 2019) - Zhang, Yan; Xia, Xinhui; Liu, Bo; Deng, Shengjue; Xie, Dong; Liu, Qi; Wang, Yadong; Wu, Jianbo; Wang, Xiuli; Tu, Jiangping
Abstract: Scrupulous design and smart hybridization of bespoke electrode materials are of great importance for the advancement of sodium ion batteries (SIBs). Graphene‐based nanocomposites are regarded as one of the most promising electrode materials for SIBs due to the outstanding physicochemical properties of graphene and positive synergetic effects between graphene and the introduced active phase. In this review, the recent progress in graphene‐based electrode materials for SIBs with an emphasis on the electrode design principle, different preparation methods, and mechanism, characterization, synergistic effects, and their detailed electrochemical performance is summarized. General design rules for fabrication of advanced SIB materials are also proposed. Additionally, the merits and drawbacks of different fabrication methods for graphene‐based materials are briefly discussed and summarized. Furthermore, multiscale forms of graphene are evaluated to optimize electrochemical performance of SIBs, ranging from 0D graphene quantum dots, 2D vertical graphene and reduced graphene oxide sheets, to 3D graphene aerogel and graphene foam networks. To conclude, the challenges and future perspectives on the development of graphene‐based materials for SIBs are also presented. Abstract : The recent progress of multiscale graphene‐based electrode materials for application in sodium ion batteries in respect of electrode design principle, preparation methods, characterization, synergistic effects, and electrochemical performance is reviewed, and future challenges and prospects of the field are presented.